Association between circulating oxidised low-density lipoprotein and fibrocalcific remodelling of the aortic valve in aortic stenosis. Issue 9 (11th October 2007) - Côté, C; Pibarot, P; Després, J-P; Mohty, D; Cartier, A; Arsenault, B J; Couture, C; Mathieu, P
Abstract : Introduction: Aortic stenosis (AS) is the most common valvular heart disease in westernised societies. AS is a disease process akin to atherosclerosis in which calcification and tissue remodelling play a crucial role. In patients with moderate/severe AS, we sought to determine whether the remodelling process would be in relationship with transvalvular gradients and circulating oxidised low-density lipoprotein (ox-LDL) levels. Methods: In 105 patients with AS, the aortic valve and blood plasma were collected at the time of valve replacement surgery. The degree of valve tissue remodelling was assessed using a scoring system (Score: 1-4) and the amount of calcium within the valve cusps was determined. The standard plasma lipid profile, the size of LDL particles and the plasma level of circulating ox-LDL (4E6 antibody) were determined. Results: After adjustment for covariables, aortic remodelling score was significantly related to transvalvular gradients measured by Doppler echocardiography before surgery. Patients with higher valve remodelling score had higher circulating ox-LDL levels (score 2: 27.3 (SEM 2.6) U/l; score 3: 32.2 (SEM 2.3) U/l; score 4: 38.3 (SEM 2.3) U/l; p = 0.02). After correction for age, gender, hypertension and HDL-C, the plasma level of ox-LDL remained significantly associated with the aortic valve remodelling score (p<0.001). The plasma level of ox-LDL was significantly associated with LDL-C (r = 0.41; p<0.001), apoB (r = 0.59; p<0.001), triglyceride (r = 0.39; p<0.001), Apo A-I (r = 0.23; p = 0.01) and cholesterol in small (<255 Å) LDL particles (r = 0.22; p = 0.02). After correction for covariables, circulating ox-LDL levels remained significantly associated with apoB (p<0.001) and triglyceride (p = 0.01) levels. Conclusion: Increased level of circulating ox-LDL is associated with worse fibrocalcific remodelling of valvular tissue in AS. It remains to be determined whether circulating ox-LDL is a risk marker for a highly atherogenic profile and/or a circulating molecule which is actively involved in the pathogenesis of calcific aortic valve disease.